1981
DOI: 10.1002/ajh.2830110210
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of platelet function tests

Abstract: Methods for the standardization of several currently used platelet function tests (bleeding time, capillary fragility, platelet retention, platelet aggregation, platelet factor 3, and platelet volume profiles) are presented, Different variables than may interfere with the reproducibility of the results of each assay were identified and standardized. Using the standardized techniques, the range of normal values for each test was determined in a large population of normal volunteers and used to identify disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 81 publications
1
7
0
Order By: Relevance
“…In a recent study, 9 aggregation of platelet count‐adjusted PRP (250/nl) did not differ from native PRP (348/nl to 711/nl), but higher platelet concentrations (1258 × 10 3 to 1535/nl) increased the aggregation response. Conversely, LTA was shown to be correlated to the platelet count in adjusted samples below 200/nl 10,11 . These findings implicate platelet count as an important topic in aggregation studies.…”
Section: Discussionmentioning
confidence: 77%
“…In a recent study, 9 aggregation of platelet count‐adjusted PRP (250/nl) did not differ from native PRP (348/nl to 711/nl), but higher platelet concentrations (1258 × 10 3 to 1535/nl) increased the aggregation response. Conversely, LTA was shown to be correlated to the platelet count in adjusted samples below 200/nl 10,11 . These findings implicate platelet count as an important topic in aggregation studies.…”
Section: Discussionmentioning
confidence: 77%
“…These parameters are now readily available on many automated platelet particle counters. [209][210][211] With the current trend of using antiplatelet agents as prophylaxis for thrombotic events, modalities to assess the efficacy of antiplatelet therapy are needed; platelet indices and platelet size distributions may give a reasonable clinical indication of response to antiplatelet therapy. [212][213][214] As platelets become activated, there is release of platelet factor 4 (PF4), beta-thromboglobulin (BTG), and thromboxane A 2 and as platelets are consumed, subsequent to activation, large young platelets are anticipated in the peripheral blood.…”
Section: Hyperactive Prethrombotic Plateletsmentioning
confidence: 99%
“…CPT induces a reversible breakage of DNA in vivo (24,25) and in vitro (28). CPT is also reported to inhibit DNA synthesis in L5178Y and HeLa cells (38) and to be more cytotoxic to the cells in S phase than in G1 or G2 phase (39,40). In vitro studies have demonstrated that topoisomerase I is required for the elongation step of adenovirus DNA replication (41).…”
mentioning
confidence: 99%